The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s12033-010-9292-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the CMV-IE Promoter by Hyperthermia In Vitro and In Vivo: Biphasic Heat Induction of Cytosine Deaminase Suicide Gene Expression

Abstract: The cytomegalovirus-immediate early (CMV-IE) promoter is widely used as a strong and constitutively active promoter. Although the CMV-IE promoter does not harbor heat-responsive sequences, we determined its heat inducibility. We analyzed in vitro and in vivo heat responsiveness and possible mechanisms of heat induction of the CMV-IE promoter. We used transfected SW480 human colon carcinoma cells (SW480/CMVCD), expressing CMV-IE promoter-driven bacterial cytosine deaminase (CD) gene. These cells were heated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It can induce growth arrest by interacting with CDK2 and CDK4 and interacts with the heterodimer E2F-DP to inhibit cell growth [66], [67]. To date, little is known about its function in CMV infection, however, the MIEP promoter of CMV contains a binding site for this transcription factor [68].…”
Section: Resultsmentioning
confidence: 99%
“…It can induce growth arrest by interacting with CDK2 and CDK4 and interacts with the heterodimer E2F-DP to inhibit cell growth [66], [67]. To date, little is known about its function in CMV infection, however, the MIEP promoter of CMV contains a binding site for this transcription factor [68].…”
Section: Resultsmentioning
confidence: 99%
“…We also noted that heat induction of hGM-CSF expression is more obvious in Hep3B cells than in A549 cells, suggesting cell type dependence. Recently, the stimulating effect of heat stress on CMV promoter activity has been studied [21,22]. Although the possible mechanisms might be complex, a considerable homology to the heat stress element core consensus (GA–TCC) within 18 bp elements in IE enhancer might be the most reasonable explanation [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the stimulating effect of heat stress on CMV promoter activity has been studied [21,22]. Although the possible mechanisms might be complex, a considerable homology to the heat stress element core consensus (GA–TCC) within 18 bp elements in IE enhancer might be the most reasonable explanation [21,23]. Heat stress might regulate CMV-IE activity directly and indirectly through heat-activated transcription factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated a high promoter activity of the WSSV IE gene ie1 in Sf9 insect cells [44]. Its promoter activity for gene expression in insect cells is stronger than that of the cytomegalovirus (CMV) IE promoter, which is widely used as a strong and constitutively active promoter [45,46]. [36] The unprecedented worldwide spread of highly pathogenic avian influenza viruses of the H5N1 strain is currently considered a global health concern that has provoked significant mortalities in poultry and wild bird's populations.…”
Section: Using Marine Viruses Genetic Properties To Treat Diseasesmentioning
confidence: 99%